Countersolvent Electrolytes for Lithium‐Metal Batteries. Issue 10 (7th February 2020) - Piao, Nan; Ji, Xiao; Xu, Hong; Fan, Xiulin; Chen, Long; Liu, Sufu; Garaga, Mounesha N.; Greenbaum, Steven G.; Wang, Li; Wang, Chunsheng; He, Xiangming
Abstract: Development of electrolytes that simultaneously have high ionic conductivity, wide electrochemical window, and lithium dendrite suppression ability is urgently required for high‐energy lithium‐metal batteries (LMBs). Herein, an electrolyte is designed by adding a countersolvent into LiFSI/DMC (lithium bis(fluorosulfonyl)amide/dimethyl carbonate) electrolytes, forming countersolvent electrolytes, in which the countersolvent is immiscible with the salt but miscible with the carbonate solvents. The solvation structure and unique properties of the countersolvent electrolyte are investigated by combining electroanalytical technology with a Molecular Dynamics simulation. Introducing the countersolvent alters the coordination shell of Li + cations and enhances the interaction between Li + cations and FSI − anions, which leads to the formation of a LiF‐rich solid electrolyte interphase, arising from the preferential reduction of FSI − anions. Notably, the countersolvent electrolyte suppresses Li dendrites and enables stable cycling performance of a Li||NCM622 battery at a high cut‐off voltage of 4.6 V at both 25 and 60 °C. This study provides an avenue to understand and design electrolytes for high‐energy LMBs in the future. Abstract : A countersolvent electrolyte enhances the interaction between the Li + cations and FSI − anions, thereby contributing to the formation of a FSI − anion‐derived LiF‐rich solid electrolyte interphase. This electrolyte has a high ionic conductivity, a wide electrochemical window, and inhibits the formation of lithium dendrites which may aid in the development of robust high‐energy lithium‐metal batteries.